The modest alcohol consumption reduces the incidence of fatty liver in men: a population‐based large‐scale cohort study. Issue 3 (March 2015) - Hashimoto, Yoshitaka; Hamaguchi, Masahide; Kojima, Takao; Ohshima, Yasuhiro; Ohbora, Akihiro; Kato, Takahiro; Nakamura, Naoto; Fukui, Michiaki
Abstract Background and Aim Recent cross‐sectional studies have been reported the possibility that light to moderate alcohol consumption might be negatively associated with fatty liver. However, there has been no large‐scale longitudinal study addressing an impact of alcohol consumption on a development of fatty liver diagnosed by ultrasonography. Thus, we investigated the impact of alcohol consumption on a natural history of fatty liver. Methods We analyzed 5437 apparently healthy Japanese who received the health checkup programs repeatedly over 10 years. In this study, we used a standardized questionnaire for addressing the medical history and lifestyle and used a standardized ultrasonographic diagnosis for fatty liver. The total amount of alcohol consumed per week was calculated and classified into four grades; none or minimal, light, moderate, or heavy alcohol consumption (< 40, 40–140, 140–280 or > 280 g/week, respectively). The hazard risks of alcohol consumption for the development of fatty liver were calculated by Cox hazard model after adjusting age, BMI, and parameters for lifestyle. Results During 10 years of follow‐up, fatty liver was continuously diagnosed just in 10% of men and 20% of women with fatty liver at the baseline. In men, the adjusted hazard risks of light and moderate alcohol consumption for the development of fatty liver were 0.72 (95% confidence interval 0.60–0.86, P < 0.001) and 0.69 (0.57–0.84, P < 0.001), respectively. However, they were not significant in women. Conclusions The newly onset of fatty liver was significantly repressed in apparently healthy men who consume light to moderate alcohol.